Consumer’s Satisfaction Assessment for Service Quality by Servqual Method (Study Case at “Waroeng X“Soekarno Hatta-Malang Branch) - Mustaniroh, Siti Asmaul; Lestari, Endah Rahayu; Sari, Eko Natalia (Jurnal Teknologi Pertanian, 2010)
â€œWaroeng Xâ€ is one of restaurants in Malang that provide steaks and drinks that not only give productâ€™s quality and quantity, but also give a good service in order to get constumers. The purpose of this research is to define the level of consumerâ€™s satisfaction toward service quality by servqual method approach and to know the major priority attributes â€œWaroeng Xâ€ Soekarno Hatta-Malang branch. The results showed that all of dimensions had a negative satisfaction value, including un-satisfaction categories. Satisfaction value of each dimensions were, reliability of -0,136; responsiveness of -0,117; assurance of -0,173; empathy of -0,096; and tangibles evidence of -0,078. The major priority attributes in service quality improvements were: service time, productâ€™s and serveâ€™s quality, price, Â empathy to the consumerâ€™s complaints, pleasant and clean room, and the availability of additional facilities such as toilet, and parking area.Keywords: consumerâ€™s satisfaction, service quality, Servqual method